Lower expression of Hsa_circRNA_102682 in diabetic hyperhomocysteinemia negatively related to creatinemia is associated with TGF‐β and CTGF. Issue 8 (23rd July 2021) - Hu, Fei; Sha, Wenxin; Dai, Huixue; Yang, Xiangwei; Hu, Peng; Chu, Yudong; Qiu, Xiaohui; Bu, Shizhong
Abstract: Background: Diabetic nephropathy is a kidney disease caused by long‐term hyperglycemia. Hsa_circRNA_102682 is related to the pathogenesis of preeclampsia. Preeclampsia is related to hypertension and proteinuria, and diabetic nephropathy is mainly manifested by hypertension and proteinuria. The main pathological change in diabetic nephropathy is glomerular fibrosis. Methods: This study used serum samples of patients treated at Li Huili Eastern Hospital, Ningbo, China, from July 10, 2018 to February 15, 2019. We included 73 patients with diabetes and divided them into a normal‐homocysteine group and a high‐homocysteine group. We selected used quantitative reverse transcriptase‐polymerase chain reaction to measure Hsa_circRNA_102682 concentration in the serum. Serum transforming growth factor‐beta and connective tissue growth factor levels were tested using ELISA. The Pearson correlation test was used to assess the correlations between Hsa_circRNA_102682, transforming growth factor‐beta, connective tissue growth factor, homocysteine, and creatinine. Result: Hsa_circRNA_102682 was significantly lower in diabetic patients with high levels of homocysteine than in those with normal levels of homocysteine, whereas transforming growth factor‐beta and connective tissue growth factor levels were higher in diabetic patients with hyperhomocysteinemia. Hsa_circRNA_102682 was negatively correlated with the levels of transforming growth factor‐beta, connective tissue growth factor, homocysteine, and creatinine. Transforming growth factor‐beta and connective tissue growth factor were both positively correlated with homocysteine and creatinine. Conclusion: Low Hsa_circRNA_102682 was associated with high levels of transforming growth factor‐beta and connective tissue growth factor as well as homocysteine and creatinine. These results suggest that Hsa_circRNA_102682 might be related to the pathogenesis of hyperhomocysteinemia in diabetic nephropathy. Abstract : Serum levels of Hsa_circRNA_102682 in diabetic patients with normal Hcy (Normal; n = 30) and high Hcy (High; n = 43).